Managerial Ability in Managing Accountability in Financial Statements School Operational Costs at the Elementary School Level in Gorontalo City - Muchtar Ahmad; Abdurrahman Pakaya; Nurlaila Kadir; Dzakaria Lababa (Journal of International Conference Proceedings (JICP), 2018)
The purpose of the implementation of this study was to determine managerial capabilities in the management of financial statements of the School Operational Cost Funds at the Primary School level in Gorontalo City. This study uses qualitative methods. The results of this study indicate that internal and external accountability in the management of School Operational Costs funds where internal accountability is in the form of hierarchical accountability in the form of recapitulation of the budget for School Operational Costs. While the realization of the use of funds for School Operational Costs in the form of K1K7a is sent to the central management team and the overall accountability report from quarter I-IV is submitted to BAWASDA annually. Then the data entered by the Gorontalon City education service school will be sent also to the Provincial management team and the provincial School Operational Cost Management Team to send the data to the central management team. Whereas professional accountability takes the form of time for channeling school operational costs by each quarterly school or every 1 time in three months and which plays an important role in management and school operational costs, namely the principal responsible for funds for school operational costs, treasurer management of school operational costs. , the school committee is the controller and supervises the use of funds in the School Operational Costs, then the parents representatives of the students are chosen by the principal who also oversees the use of the School Operational Costs funds. External accountability is accountability beyond internal accountability such as the Regional Oversight Body (BAWASDA) which also checks the use of funds for School Operational Costs for each school and the Corruption Eradication Commission which monitors the use of school operational costs and conducts investigations, investigations and prosecutions of criminal acts corruption. While for fund management planning School Operational Costs include budget planning for School Operational Costs and HR planning for fund managers. Fund planning is arranged in the form of a fund use plan, which is prepared by the principal and treasurer of the School Operational Costs. The involvement of parents of students in the BOS budget planning is only during the preparation of the RKAS. HR planning of fund managers by forming a management team based on mutual agreement between the principal, the teacher board and the school committee taking into account the experience of the treasurer. While the selection of one of the parent’s representatives is determined by mutual agreement. To help the performance of the treasurer and the recipient team, the principal appoints one of the teachers as executive assistant to the treasurer of the School Operational Costs and the recipient of the goods. The selection of implementing assistants is based on the educational background of the undergraduate accounting and the ability to operate the computer. The implementation of fund management begins with the distribution of funds for School Operational Costs. Funding for School Operational Costs has been delayed. The delay is due to the delay of the teachers in reporting the results of activities using funds from the School Operational Costs. The mechanism for using funds begins with the submission of needs by teachers and employees, not all proposed needs can be budgeted in the RAPBS, but are filtered based on priority scale. The next step is the determination of the allocation of funding sources determined by the principal, then spent by the goods shopping team based on price standards from the District Education Office. As a final step, namely acceptance, checking and inventory of goods by the recipient team, so that ready goods / services to be used. The activity of evaluating the management of school operational costs is carried out in the form of supervision and monitoring. Supervision is carried out by principals in the form of inherent supervision, which is carried out by checking the bookkeeping of School Operational Costs, as well as providing direction in the management of Education funds. Supervision of the school committee is carried out by the head of the school committee during the school visit. Monitoring is carried out by the Gorontalo City School Operational Cost Management Team, by checking the use of funds, verifying funds with the number of students, and providing guidance on managing BOS funds. In monitoring activities, complaints are not handled, because schools do not receive complaints from any party. Factors influencing managerial ability in managing accountability of financial statements of the School Operational Cost Fund at the Elementary School Level, in general from competency factors, experience, training and motivation of the boss fund managers. Keywords: Managerial Ability, and Financial Report Accounting